Equitable access to ectogenesis for sexual and gender minorities. (12th February 2020) - Kimberly, Laura L.; Sutter, Megan E.; Quinn, Gwendolyn P.
Abstract: As the technology for ectogenesis continues to advance, the ethical implications of such developments should be thoroughly and proactively explored. The possibility of full ectogenesis remains hypothetical at present, and myriad concerns regarding the safety and efficacy of the technology must be evaluated and addressed, while pressing moral considerations should be fully deliberated. However, it is conceivable that the technology may become sufficiently well established in the future and that eventually full ectogenesis might be deemed ethically acceptable as a reproductive alternative to gestation within a human womb under certain circumstances. If the safety and efficacy of full ectogenesis are established, if ethical dilemmas are sufficiently well addressed, and if the technology is offered as a reproductive option to cisgender heterosexual individuals or couples desiring to become parents, there is a moral obligation grounded in social justice to ensure that full ectogenesis be made available to individuals or couples identifying as members of sexual‐ or gender‐minority groups who likewise seek to pursue parenthood. We examine the history of access to current family‐building options, including assisted reproductive technology, surrogacy and adoption, for these populations and conclude that in the absence of robust empirical evidence suggesting an increased risk of harm to children of individuals and couples who identify as members of sexual‐ or gender‐minority groups, equitable access to ectogenesis as a pathway to parenthood for sexual and gender minorities must be assured as a matter of reproductive justice.